2020
DOI: 10.20884/1.sar.2020.5.2.3554
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Company Value Information, Dividend Policy, and Capital Structure on Stock Price

Abstract: This study aims to examine: 1) The effect of company value information in this case the price book value (PBV) on stock prices, 2) The effect of dividend policy in this case the dividend payout ratio (DPR) on stock prices, 3) The effect of capital structure in terms of This is a debt to equity ratio (DER) to stock prices. This type of research is classified as research that is causative. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2008 to 2010. The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
1
4
1
6
Order By: Relevance
“…This is consistent with the findings of Allen and Rachim (1996), Hussainey et al (2011), Lucas and McDonald (1990), Profilet (2013). Our findings are contrary to the study of Syofyan et al (2020), Zainudin et al (2018) which found positive and significant relationship between the dividend payout and the stock price volatility. Our results also showed a positive but insignificant relationship between dividend yield and dividend per share with the stock volatility which are similar to the findings of Allen and Rachim (1996), Lotfi (2018).…”
Section: Conclusion and Final Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the findings of Allen and Rachim (1996), Hussainey et al (2011), Lucas and McDonald (1990), Profilet (2013). Our findings are contrary to the study of Syofyan et al (2020), Zainudin et al (2018) which found positive and significant relationship between the dividend payout and the stock price volatility. Our results also showed a positive but insignificant relationship between dividend yield and dividend per share with the stock volatility which are similar to the findings of Allen and Rachim (1996), Lotfi (2018).…”
Section: Conclusion and Final Discussioncontrasting
confidence: 99%
“…Seyedimany (2019) investigated companies listed on NASDAQ for the period of 2014–2018 and found that the dividend announcement has no significant impact on stock price for the companies listed on NASDAQ. Syofyan et al (2020) investigated the companies listed on the Indonesia Stock Exchange in the period 2008–2010 and found that stock prices have significant positive relation with the dividend policies of the companies. Farooq and ElBannan (2019) investigated Indian market for the period between 2000 and 2012 for their study and found that positive relationship between stock price synchronicity and dividend payout ratios breaks down at major levels of synchronicity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analisis kebangkrutan sangat penting bagi berbagai pihak. Seperti halnya investor akan menggunakan informasi kebangkrutan yang bersumber dari laporan keuangan perusahaan untuk mengawasi investasi yang dilakukannya (Syofyan et al, 2020). Analisis kebangkrutan digunakan untuk memperoleh tanda-tanda awal (Hanafi & Halim, 2016).…”
Section: Gambar 1 Pergerakan Profit Perusahaan Sub Sektor Transportasiunclassified
“…Penelitian terdahulu yang dilakukan oleh Syofyan et al (2020) menyebutkan bahwa DPR memiliki pengaruh positif terhadap abnormal return yang digambarkan dalam pergerakan harga saham. Hal tersebut sejalan dengan teori sinyal dikarenakan distribusi dividen tersebut dapat menjadi sinyal bagi investor bahwa perusahaan mampu untuk menghasilkan keuntungan dalam jangka waktu yang panjang kedepannya.…”
Section: Abnormal Returnunclassified
“…dilakukan olehSyofyan et al (2020),Triana & Lukman (2021),Fu & Blazenko (2015),Yahyaee(2015),Cuong & Ngoc (2016) menyatakan bahwa kebijakan dividen memiliki pengaruh terhadap abnormal return. Selain itu penelitian yang dilakukan oleh olehFelicia & Salim (2019) yang menyatakan bahwa kebijakan dividen memiliki pengaruh negatif terhadap abnormal return.…”
unclassified